Jak3-Independent Trafficking of the Common γ Chain Receptor Subunit: Chaperone Function of Jaks Revisited - Hofmann, Sigrun R. (American Society for Microbiology, 2004)
Janus kinases (Jaks) play an essential role in cytokine signaling and have been reported to regulate plasma membrane expression of their cognate receptors. In this study, we examined whether Jak3 and the common γ chain (γ(c)) reciprocally regulate their plasma membrane expression. In contrast to interleukin-2Rα, γ(c) localized poorly to the plasma membrane and accumulated in endosomal-lysosomal compartments. However, γ(c) was expressed at comparable levels on the surface of cells lacking Jak3, and plasma membrane turnover of γ(c) was independent of Jak3. Nonetheless, overexpression of Jak3 enhanced accumulation of γ(c) at the plasma membrane. Without γ(c), Jak3 localized in the cytosol, whereas in the presence of the receptor, it colocalized with γ(c) in endosomes and at the plasma membrane. Although the Jak FERM domain is necessary and sufficient for receptor binding, the requirement for full-length Jak3 in γ(c) membrane trafficking was remarkably stringent; using truncation and deletion mutants, we showed that the entire Jak3 molecule was required, although kinase activity was not. Thus, unlike other cytokine receptors, γ(c) does not require Jak3 for receptor membrane expression. However, full-length Jak3 is required for normal trafficking of this cytokine receptor/Jak pair, a finding that has important structural and clinical implications.